Pharmacotherapy of Vitreomacular Traction - Wan, Ran; Hong, Thomas; Tariq, Yasser; Chang, Andrew (Current Pharmaceutical Design, 2018)
Vitreomacular traction occurs due to incomplete or anomalous posterior vitreous detachment. Over time, the vitreous pulls anteriorly and causes retinal distortion and eventually reduced vision. Traditionally, vitreomacular traction was treated with vitrectomy surgery. In the past few years, there is a paradigm shift towards pharmacologic vitreolysis, which involves the intravitreal injection of enzymatic and non-enzymatic agents that facilitate posterior vitreous detachment. Many agents have been investigated and trialled including plasmin, microplasmin (Ocriplasmin), hyaluronidase, nattokinase, chondroitinase and dispase. This review will focus on the progress and current status in this research.
Keywords: ocriplasmin